Effect of gamma-gamma distribution on performance of optical differential 8-level phase shift keying in free space optical communication - Boroon, Mohammad (2016)
The work in this thesis focuses on performance analysis of optical differential 8-level phase shift keying (OD8PSK) in free space optical (FSO) communication. The current FSO connections lack reasonable throughput and reliable communication.For long, researchers studied this vast area of optics to ensure connectivity at last mile to fiber infrastructure. Simulation analysis using an electrically coded OD8PSK and bi-level receiver containing 4 delay and add filters (DAFs) is chosen. Gammagamma distribution is utilized to account for scintillation regime throughout FSO transmission. Numerical investigation using two well-known semi-analytical methods namely Chi-squared representation and Karhunen-Loeve series expansion (KLSE) is conducted. These methods analyze performance of OD8PSK in different aspects to bring the most reliable outcomes. Using Chi-squared representation, the sensitivity limits of OD8PSK receiver in presence of gamma-gamma fading is investigated. This method shows for the worst bit error rate (BER), additional 21.8 photons/bit are required to maintain BER = 10-9. This cause increment of 2.18 dB optical signal to noise ratio (OSNR) limit comparing to back-to-back OD8PSK and additional 8.12 dB power penalty comparing to traditional fiber models to triple spectral efficiency. Investigation of distance allowance is done by KLSE BER analysis. Using the OSNR reading of simulation results and utilizing the KLSE, The maximum permissible distance at which OD8PSK FSO can operate while maintaining BER of 10-9 is 1.53, 1.64, 1.72 and 1.83 km for scintillation intensities of 10-12, 10-13, 10-14 and 10-15 m-2/3 respectively. Finally phase offset error analysis of DAFs is conducted by investigating the sensitivity penalty at the receiver. OD8PSK in FSO is proven to tolerate 0.75º of phase error for 1 dB sensitivity penalty for BER of 10-9.